(untitled) (The Research of Medical Science Review, 2025)
Background: Chronic Hepatitis C Virus (HCV) infection is commonly associated with type 2 diabetes mellitus (T2DM), often leading to insulin resistance and worsened glycemic control. Direct-acting antivirals (DAAs) have been shown to effectively eradicate HCV, but their impact on glycemic control in diabetic patients remains unclear. This study aims to investigate the relationship between successful HCV treatment and glycemic control in patients with T2DM. Objectives: To evaluate the effect of achieving sustained virologic response (SVR) on glycemic control, as measured by HbA1c levels, in patients with both HCV and T2DM. Study Design & Setting: This was a cross-sectional, observational study conducted at the Department of Gastroenterology, King Edward Medical University and Mayo Hospital, Lahore from December 2024 to May 2025. The study included 116 patients with HCV and T2DM who were treated with DAAs. Methodology: Patients were stratified based on whether they achieved SVR. Demographic and clinical data were collected, and HbA1c levels were measured at baseline and at 12 weeks post-treatment. Data were analyzed using statistical tests, including t-tests and chi-square tests, with a significance threshold of p < 0.05. Results: Patients who achieved SVR showed a significant reduction in HbA1c levels (p < 0.001), with a greater improvement in glycemic control compared to those who did not achieve SVR. Additionally, a significant difference in smoking status was observed between the two groups (p = 0.022). Conclusion: Successful HCV treatment with DAAs significantly improves glycemic control in patients with T2DM, particularly among those who achieve SVR. Smoking status was found to be a potential effect modifier.